Novel evidence on sepsis-inducing pathogens: from laboratory to bedside - Gatica, Sebastian; Fuentes, Brandon; Rivera-Asín, Elizabeth; Ramírez-Céspedes, Paula; Sepúlveda-Alfaro, Javiera; Catalán, Eduardo A.; Bueno, Susan M.; Kalergis, Alexis M.; Simon, Felipe; Riedel, Claudia A.; Melo-Gonzalez, Felipe (Frontiers in Microbiology, 2023)
Sepsis is a life-threatening condition and a significant cause of preventable morbidity and mortality globally. Among the leading causative agents of sepsis are bacterial pathogens Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, Pseudomonas aeruginosa, and Streptococcus pyogenes, along with fungal pathogens of the Candida species. Here, we focus on evidence from human studies but also include in vitro and in vivo cellular and molecular evidence, exploring how bacterial and fungal pathogens are associated with bloodstream infection and sepsis. This review presents a narrative update on pathogen epidemiology, virulence factors, host factors of susceptibility, mechanisms of immunomodulation, current therapies, antibiotic resistance, and opportunities for diagnosis, prognosis, and therapeutics, through the perspective of bloodstream infection and sepsis. A list of curated novel host and pathogen factors, diagnostic and prognostic markers, and potential therapeutical targets to tackle sepsis from the research laboratory is presented. Further, we discuss the complex nature of sepsis depending on the sepsis-inducing pathogen and host susceptibility, the more common strains associated with severe pathology and how these aspects may impact in the management of the clinical presentation of sepsis.